Lower limb deep venous thrombosis due to vertebral osteophyte: a May-Thurner-like syndrome - Aydın, Hasan; Engin, Mesut (The European Research Journal, 2020)
Lower extremity venous thrombosis is a risky condition that may cause crucial complications including pulmonary embolism and post-thrombotic syndrome. May-Thurner syndrome is a venous compression syndrome resulting in compression of the left common iliac vein by the overriding right iliac artery. In this case, left common iliac vein compression arises from the vertebral osteophyte.